2016
DOI: 10.1039/c5cy00646e
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen oxide removal over hydrotalcite-derived mixed metal oxides

Abstract: Rigorous regulations of nitrogen oxide emissions require the development of technologies for their removal from exhaust gases. Implementation of appropriate catalysts can potentially promote NO x (NO, NO 2 ) or N 2 O removal in shorter reaction time and under milder operation conditions. However, several challenges have to be faced upon trying to address nitrogen oxide pollution with catalytic systems such as sufficient catalytic performance, suitable operational temperatures and catalyst poisoning. The flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
48
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(52 citation statements)
references
References 165 publications
0
48
0
Order By: Relevance
“…Despite intensive research on suitable technologies for N 2 O abatement, targeted catalyst development in which the effects of inhibiting compounds are considered is limited. Co‐containing, hydrotalcite‐derived mixed metal oxides are one of the most efficient catalysts for N 2 O decomposition (deN 2 O) . In early studies, Kannan and Swamy investigated several combinations of M 2+ /Mg, Co, Ni, Cu, or Zn and M 3+ /Al, Fe, or Cr together with different M 2+ /M 3+ molar ratios.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite intensive research on suitable technologies for N 2 O abatement, targeted catalyst development in which the effects of inhibiting compounds are considered is limited. Co‐containing, hydrotalcite‐derived mixed metal oxides are one of the most efficient catalysts for N 2 O decomposition (deN 2 O) . In early studies, Kannan and Swamy investigated several combinations of M 2+ /Mg, Co, Ni, Cu, or Zn and M 3+ /Al, Fe, or Cr together with different M 2+ /M 3+ molar ratios.…”
Section: Introductionmentioning
confidence: 99%
“…found that the presence of Mg in CoMgAl‐O x (Co/Mg/Al=2:1:1, 1:2:1 mol %) improved the textural properties of the materials and eliminated the initial deactivation of the catalysts in the presence of SO 2 and O 2 . Furthermore, the incorporation of noble metals, especially Rh with 0.7 wt % loading, within the brucite‐like layers of the precursors led to the superior activity of mixed metal oxides; however, their high cost (rhodium nitrate was the most efficient precursor) limits their applicability . Furthermore, Ag‐doped materials have been investigated extensively for the selective oxidation of methanol, the epoxidation of ethylene, and the selective catalytic reduction (SCR) of NO x , whereas their use in N 2 O reduction or decomposition remains relatively rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two-dimensional layered double hydroxide (LDH)-derived MMOs have recently attracted widespread attention because of their special two-dimensional structures, higher active sites, and specific surface areas [22,23,24]. For example, two-dimensional (2D) Co-Al MMOs that are derived from LDH have been investigated as a potential catalyst for NO x removal at high temperatures of 750 °C in the presence of oxygen and water [25].…”
Section: Introductionmentioning
confidence: 99%
“…The commercial catalysts V2O5-WO3/TiO2 and V2O5-WO3 (MO3)/TiO2 were widely used as NH3-SCR in stationary engines exhaust, encounter difficulties such as ammonia slip, air heater fouling, ammonium sulfate deposition and being hazardous not a good choice for vehicular engines. Cu-ZSM-5 and Fe-ZSM-5 are highly active and stable at high temperatures but hydrothermally unstable make them not viable for commercial applications [14].…”
Section: Introductionmentioning
confidence: 99%